The growing void in the U.S. homeowners insurance market: who should bear the rising cost of climate change? - Mona Hemmati; Ian P. Gray; Steven G. Bowen (npj Climate Action)
Abstract Homeowner insurance is a cornerstone of modern society. It underpins broader housing markets, provides financial security for families and individuals, and is a source of resilience for communities recovering from disasters. However, climate change and urban development in hazard-prone areas are undermining this critical institution, forcing private insurers to retreat from high-risk regions and leaving homeowners in the lurch precisely when they are most in need of coverage. This perspective explores the cascading effects of this crisis and advocates for a multi-faceted set of reforms that address three interrelated problem domains—enhancing innovations in pricing and underwriting, improving transparency of data and risk assessment practices, and bolstering resilience of the built environment—to ensure sustainable protection for the future.